PERTUMBUHAN DAN PRODUKSI TANAMAN BAWANG MERAH (Allium Ascalonicum L) TERHADAP PEMBERIAN KOMPOS RUMPUT GAJAH DAN PUPUK KCl - Siregar, Khusnu Abdillah; Edward Bahar; Ariski Ardiansyah (Universitas Pasir Pengaraian, 2024)
Khusnu Abdillah Siregar, Growth And Production Of Onion (Allium Ascalonicum L) Against By Giving Elephant Grass Compost And KCL Fertilizer. Guided by Mr. Khusnu Abdillah Siregar, SP., MP and Mr Ir. Edward Bahar, MP., Ph.D, this research has been carried out at the Kasa House of the Faculty of Agriculture, Agrotechnology Study Program, Pasir Pengaraian University, Kumu Rambah Hilir Village, Rokan Hulu Regency. This study used a Factorial Complete Randomized Design (RAL) consisting of two factors. The first factor is the provision of Elephant Grass Compost consisting of 4 levels and the second factor is the provision of KCl which consists of 4 levels so that 16 combinations of treatments with 3 repetitions are obtained, so there are 48 experimental units. Each experimental unit (plot) consists of 6 plants and 3 plants are used as research observation samples so that the entire experimental unit is 288 plants. The results can be concluded that the interaction of elephant grass and KCl fertilizer has a significant effect on plant height, harvest age, number of tubers per clump, number of leaves, wet tuber weight and dry tuber weight. The best treatment was a combination dose of elephant grass elephant grass 60 g/ and KCl fertilizer 0.12 g / (G3K3). The main effect of real elephant grass compost on all observation parameters. The best treatment is a dose of elephant grass compost 60 g per (G3).